Obstetric hysterectomy: a receding trend - Tasneem, Fasiha; Shanbhag, Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Over 500,000 women die each year due to complications of pregnancy and childbirth, a number that has remained relatively unchanged since 1990, when the first global estimates of the burden of maternal mortality were developed. Hemorrhage due to uterine atony, adherent placenta and PPH are still the causes of maternal death in developing countries. Although advances have been made in the development of conservative medical and surgical treatment of obstetric haemorrhage like brace sutures, internal iliac artery ligation, selective arterial embolization etc emergency obstetric hysterectomy remains a lifesaving procedure in the management of intractable haemorrhage unresponsive to conservative management.